Multiple occupancy-abundance patterns in staghorn coral communities - Richards, Zoe; Syms, C.; Wallace, C.; Muir, P.; Willis, B. (Blackwell Science Ltd, 2013)
Aim: Understanding patterns in a species' occupancy and abundance across multiple scales is important for management purposes, particularly for protecting threatened species. Here, we develop a new quantitative, multiscale model of occupancy and abundance that characterizes seven types of rarity and one of commonness in high-diversity communities of staghorn coral. We examine how rare species influence coral community structure and explore spatial variability in underlying patterns of community structure in the context of optimizing the data needed to protect biodiversity. Location: North-west Pacific Ocean. Methods: We present categorical abundance data for 87 species of staghorn corals occurring within 100 sites across five reefs in the north-west Pacific Ocean. We develop a new model that combines measures of global distribution, local distribution and local abundance to describe eight mutually exclusive occupancy-abundance patterns, which can be used to prioritize regional species conservation. Traditional and new analytical approaches are compared to explore how rare species influence multidimensional space and community structure. Results: We show that five types of occupancy-abundance relationships exist in staghorn coral assemblages, including four patterns of rarity. The overwhelming majority of species (73%) are rare according to local abundance and/or distribution criteria. Occupancy-abundance patterns are spatially variable in staghorn coral communities, and no single underlying distribution fits all assemblages. Our findings suggest that 54 species are at risk of regional extinction, 30 of which are also classified as 'vulnerable' by the IUCN. Main conclusions: Our model demonstrates that multiple occupancy-abundance patterns exist in staghorn coral assemblages. We conclude that 66% of the pool of staghorn coral fauna in the north-west Pacific is at risk of regional extinction. At the locations and scales examined here, occupancy-abundance patterns and the underlying distributions of coral communities are spatially variable, suggesting that it may not be appropriate to apply unified ecological theory to communities with a large proportion of threatened species because this may jeopardize biodiversity conservation. © 2013 John Wiley & Sons Ltd.